We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+5
355
2
avatar+266 

-3x-2y=-12

9x+6y=-9

 Oct 14, 2015

Best Answer 

 #2
avatar+23048 
+10

-3x-2y=-12

9x+6y=-9

 

\(\text{Determinante }~D=\begin{vmatrix} -3 && -2 \\ 9 && 6 \end{vmatrix} =(-3)\cdot 6 - 9\cdot (-2)= -18+18 = 0\\ D = 0 \qquad \Rightarrow \qquad \text{ no solution }\)

 

laugh

 Oct 14, 2015
 #1
avatar+103059 
+5

-3x-2y=-12    divide everything by 2  →  ( -3/2 )x - y = -6
9x+6y=-9      divide everything by  6  →  (3/2)x + y = -3/2

 

Add these equations together

 

0 + 0 = -6 - 3/2

 

0 = - 15/2    

 

This is never true.....so.....this system has no solution, Paypay

 

 

cool cool cool

 Oct 14, 2015
 #2
avatar+23048 
+10
Best Answer

-3x-2y=-12

9x+6y=-9

 

\(\text{Determinante }~D=\begin{vmatrix} -3 && -2 \\ 9 && 6 \end{vmatrix} =(-3)\cdot 6 - 9\cdot (-2)= -18+18 = 0\\ D = 0 \qquad \Rightarrow \qquad \text{ no solution }\)

 

laugh

heureka Oct 14, 2015

29 Online Users

avatar
avatar
avatar
avatar
avatar